Inhibition of H1N1 influenza virus-induced apoptosis by selenium nanoparticles functionalized with arbidol through ROS-mediated signaling pathways. Issue 27 (10th June 2019) - Li, Yinghua; Lin, Zhengfang; Gong, Guifang; Guo, Min; Xu, Tiantian; Wang, Changbing; Zhao, Mingqi; Xia, Yu; Tang, Ying; Zhong, Jiayu; Chen, Yi; Hua, Liang; et al.
Abstract : As an effective antiviral agent, the clinical application of arbidol is limited by the appearance of drug-resistant viruses. Abstract : As an effective antiviral agent, the clinical application of arbidol is limited by the appearance of drug-resistant viruses. To overcome the limitation of drug-resistance, the use of modified nanoparticles with biological materials to explore novel anti-influenza drugs is developing rapidly. The antiviral activity of selenium nanoparticles (SeNPs) has attracted increasing attention in the biomedical field. Surface modified SeNPs by arbidol (Se@ARB) with superior antiviral properties towards drug resistance are synthesized in the current study. Arbidol decoration of SeNPs (Se@ARB) with less toxicity had obviously inhibited H1N1 infection. Se@ARB interfered with the interaction between the H1N1 influenza virus and the host cells by suppressing the activity of hemagglutinin (HA) and neuraminidase (NA). Se@ARB could prevent H1N1 from infecting MDCK cells and block DNA fragmentation and chromatin condensation. Furthermore, Se@ARB evidently inhibited the generation of reactive oxygen species (ROS). In vivo experiments revealed that Se@ARB prevents lung injury in H1N1 infected mice through hematoxylin and eosin staining. The TUNEL test of lung tissues shows that DNA damage reached a high level but reduced substantially when treated with Se@ARB. Immunohistochemical assay revealed that activation of caspase-3, AKT and MAPK signaling pathways was restrained by Se@ARB treatment. These results demonstrate that Se@ARB is a promising antiviral pharmaceutical candidate for the inhibition of H1N1 influenza virus.